Influence of Western Television Programmes on Lifestyle of Youths in Nepal - Panth, Keshav (Nepalese Journal of Business, 2024)
This study examines influence of western television programs on lifestyle of youths in Nepal. Lifestyle is selected as the dependent variable. The independent variables are enjoyment, eating habits, smoking and alcohol consumption, informativeness and violent scenes. The primary source of data is used to assess the opinions of the respondents regarding Influence of western television programmes on lifestyle of youths in Nepal. The study is based on primary data with 121 respondents. To achieve the purpose of the study, 35 structured questionnaires were prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors associated with Influencing factors of western television programmes on lifestyle of youths in Nepal. The study showed that enjoyment has a positive impact on lifestyle of Nepalese youths. It indicates that higher the enjoyment, better will be the lifestyle of Nepalese youths. The result also reveals that eating habits has a positive impact on lifestyle of Nepalese youths. It indicates that better eating habits leads to better lifestyle of Nepalese youths. Similarly, informativeness has a positive impact on lifestyle of Nepalese youths. It indicates that higher the informativeness, better will be the lifestyle of Nepalese youths. Likewise, smoking and alcohol consumption has a negative impact on lifestyle of Nepalese youths. It indicates that higher smoking and alcohol consumption leads to poor lifestyle of Nepalese youths. Further, violent scenes have a negative impact on lifestyle of Nepalese youths. It indicates that violent scenes lead to demolish in lifestyle of Nepalese youths.